Semantic organization in children with cochlear implants: computational analysis of verbal fluency - Kenett, Yoed N.; Wechsler-Kashi, Deena; Kenett, Dror Y.; Schwartz, Richard G.; Ben Jacob, Eshel; Faust, Miriam (Frontiers in Psychology, 2013)
Purpose: Cochlear implants (CIs) enable children with severe and profound hearing impairments to perceive the sensation of sound sufficiently to permit oral language acquisition. So far, studies have focused mainly on technological improvements and general outcomes of implantation for speech perception and spoken language development. This study quantitatively explored the semantic networks of children with CIs in comparison to those of age-matched normal hearing (NH) peers. Method: Twenty seven children with CIs and twenty seven age- and IQ-matched NH children ages 7-10 were tested on a timed animal verbal fluency task (Name as many animals as you can). The responses were analyzed using correlation and network methodologies. The structure of the animal category semantic networks for both groups were extracted and compared. Results: Children with CIs appeared to have a less-developed semantic lexicon structure compared to age-matched NH peers. The average shortest path length and the network diameter measures were larger for the NH group compared to the CIs group. This difference was consistent for the analysis of networks derived from animal names generated by each group (sample-matched correlation networks) and for the networks derived from the common animal names generated by both groups (word-matched correlation networks). Conclusions: The main difference between the semantic networks of children with CIs and NH children lies in the network structure. The semantic network of children with CIs is under-developed compared to the semantic network of the age-matched NH children. We discuss the practical and clinical implications of our findings.